Profil Literasi Lingkungan Siswa Madrasah Aliyah Negeri Demak - Nanik Esti Wulandari; Fenny Roshayanti (Perkumpulan Kualitama Edukatika Indonesia, 2022)
This study aims to determine the literacy profile of the students of Madrasah Aliyah Negeri Demak. This research is a type of qualitative descriptive research. The sample in this study were 71 students of class XI MIPA Madrasah Aliyah Negeri Demak. Data collection techniques using the test method The test given to research subjects regarding environmental literacy includes four components, namely: ecological knowledge (17 multiple-choice items), skills in solving environmental problems (10 multiple-choice items), attitudes and concern for the environment (25 items). Likert scale type items), and environmentally responsible behavior (12 items). The research data were analyzed descriptively based on the achievement score criteria of each environmental literacy indicator. The results showed that the ecological knowledge component obtained an average score of 66.61%, (good) skills in solving environmental problems 40.20%, (less) attitude and concern for the environment 55.60% (enough), and responsible behavior. responsible for the environment 73, 38% (good). Skills in solving environmental problems and attitudes and care for the environment need to be improved so that the environmental literacy of MAN Demak students will be very good.